Writing Scientific Journals In The Field Of Religion And Arabic To Increase Teachers’ Professional Competence - Firman; Friscilla Tersta; Eva Iryani; Neldi Harianto (International Journal Of Community Service, 2021)
One of activities that must be carried out by teachers in developingcompetency as a teacher is scientific publication (Article 11 of the Ministerof PAN & RB Regulation No. 16 of 2009 concerning Teacher FunctionalPosition). Scientific publications are considered important in supportingthe activities of teachers by conducting scientific publications: 1) a teachersupports to improve scientific insights which are disseminated by thedevelopment of science and technology, thus the learning process carriedout daily is based on science and technology that is always up-to-date, 2)with scientific publication of a teacher is required to have insights forpublication and writing based on scientific principles, 3) with scientificpublication a teacher encourages to create and innovate in developingvarious strategies, methods, models and learning media and 4) withscientific publications teachers are required to mutually share, the resultsof research and various developments related to best practices in carryingout his profession as a teacher. For this reason, there is a need foractivities in the form of "Training of Writing Scientific Journals in the Fieldof Religion and Arabic Language to Increase the Competence ofProfessionalism in High School-Middle School Teachers in Sungai Penuh"